Public engagement by strategic science communication: an evaluation study on the impact of an interactive science exhibition on the German energy transition - Schaller, Sophia; Schumann, Christina; Wolling, Jens (Frontiers in Communication, 2025)
IntroductionScience exhibitions are a promising instrument to uniquely encourage public engagement with scientific issues. However, knowledge about the actual effectiveness of science communication activities is mostly lacking. Therefore, this study examined the impact of a science exhibition on the German energy transition on visitors’ cognitive, affective, and behavioral public engagement. Additionally, we extend knowledge on the role of gamification by examining whether an integrated game can further enhance engagement, either directly or indirectly, through positive exhibition experiences.MethodsWe used a pretest-posttest survey (N = 767 visitors at seven museum locations) to evaluate the impact of the science exhibition and the game.ResultsThe results show that the exhibition had a positive effect on cognitive and partly affective as well as behavioral engagement. For gamification, we found no positive direct effects of using the game. However, analyses revealed indirect effects on cognition and affect mediated by positive exhibition experiences.DiscussionThe findings of our study demonstrate the potential of science exhibitions as valuable tools for promoting public engagement with complex issues. Moreover, they show that future research is needed to explore how exhibitions and gamification elements can foster behavioral engagement effectively.